A família e a sociedade rural paulista: Santana de Parnaíba, 1750-1850 - Metcalf, Alida C. (Estudos Econômicos (São Paulo), 1990)
This article contrasts the family strategies of the slaveholding and peasant classes in late eighteenth and early nineteenth century Sao Paulo, Brazil. While the family strategies of slaveholders sought to preserve family property by countering the equal division of property, by encouraging the migration ofsons into the frontier, and by favoring a daughter and son-in-law with the bulk of the family estate, the family strategies of the peasantry sought simple survival in a rapidly changing rural economy. As a traditional subsistence economy gave way to a cash-crop orientation, peasant households became smaller, households headed by women increased, and nuclear families declined in importance. Adaptations and changes in family life left their mark on the social structure of the community studied as well as on the developing frontier.